Application of nanocarrier-based drug delivery system in treatment of oral cancer - Sah A.K.; Vyas A.; Suresh P.K.; Gidwani B. (My University, 2025)
Oral cancer includes cancer of lips, oral cavity and oropharynx. Oral cancer is the sixth most life-threatening disease affecting 65% of population. The delivery of cytotoxic chemotherapeutic anticancer drugs is a challenging task due to unfavorable properties. Both synthetic chemotherapeutic agents and herbal constituents are used in treatment of oral cancer. The purpose of present article is to overcome the limitations through concept of nanotechnology and conjugation approach. Also, it will provide better therapeutic effect and sustain long life of healthy and recovered cells. Moreover, development in this area will raise opportunities for the oncologist, researchers and pharmaceutical scientists. This review summarizes the clinical findings and patents on various oral anticancer drugs for effective pharmacotherapeutics. © 2017 Informa UK Limited, trading as Taylor & Francis Group.